Implementasi Perilaku Hidup Bersih dan Sehat di TK Aisyiyah Pucangan 1 Sukoharjo: Kajian Observasional tentang Kebersihan Lingkungan dan Fasilitas Kesehatan - Khuru’Aini, Loeyyina; Tejaningsih, Endah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2025)
This observational study aims to describe the implementation of health and hygiene at TK Aisyiyah Pucangan 1 Sukoharjo. The study focuses on the cleanliness of the school environment, the practice of clean and healthy living behaviours (PHBS), and the availability of sanitation facilities and health-supporting infrastructure. Data were collected through direct observation, interviews with teachers, and document analysis. The results of the study show that the institution has consistently applied hygiene standards. The school environment appears well-maintained, classrooms are well-organized, and students are accustomed to practicing clean living behaviours through teacher guidance in daily activities. However, some aspects still need improvement, such as the availability of handwashing soap, which is not always consistently maintained, and the first aid kit equipment, which is not yet fully complete. These findings emphasize the need to strengthen sanitation facilities and health services to optimally support the habit of healthy living behaviours (PHBS) in early childhood education environments.